(untitled) (Journal of Naval Architecture and Marine Engineering, 2025)
The foremost empirical of this study is to research the flow of an Upper-Convected Maxwell (UCM) fluid including nanoparticles over an elongating surface on an inclined plane. The model analyzes the impression of an external magnetic field and investigates the impacts of linear thermal radiation, a heat source, and chemical processes under various slip situations. The Homotopy Analysis Method (HAM) is employed in order to work out the nonlinear equations that regulate the system through the provision of a robust framework for the accuracy of the solution. The principal findings are displayed in tabular and graphical formats. The findings indicate that an augmentation in magnetic field strength diminishes velocity profiles while enhancing both concentration as well as temperature profiles. Moreover, as the momentum slip consideration escalates, local Sherwood number and the local Nusselt number are diminish. The innovative discoveries are validated by comparisons with previous experimental and theoretical results, demonstrating practical applications in optimizing cooling systems, improving industrial heat exchangers, and increasing biotechnological processes such as wastewater treatment and pharmaceutical manufacture. Nanofluids and non-Newtonian fluids are being portrayed as highly effective solutions for next-generation cooling technologies as a result of this research, which provided a key insight into optimizing thermal management systems for advanced engineering applications. Journal of Naval Architecture and Marine Engineering, 22(2), 2025, PP. 99-116